A Call to Revisit Classic Measurements for UX Evaluation - Schneider, Stephen; Hillman, Serena (Proceedings of the ACM Conference on Computer Supported Cooperative Work (CSCW) 2023 Workshop on Understanding & Measuring UX Outcomes at Scale, 2023)
We are user researchers supporting a variety of data and analytics products within Microsoft’s Azure Data organization. One of our prominent ongoing projects involves the comprehensive reevaluation and rejuvenation of user experience (UX) evaluation metrics. In this paper, we present a specific study conducted as part of this broader initiative, which is aimed at aligning and simplifying the System Usability Scale (SUS) for enterprise applications. The importance of updating and enhancing traditional UX measurement tools such as SUS (System Usability Scale) or UMUX Lite (Usability Metric for User Experience) cannot be overstated. Several critical factors drive the need for this ongoing evolution. Firstly, it is imperative to stay attuned to shifting user preferences in the rapidly evolving digital landscape. Secondly, adapting to the latest technological advancements is crucial to ensure the continued relevance of these metrics. Thirdly, there is a constant drive to improve measurement methods to provide more accurate and actionable insights. Additionally, aligning with stakeholder needs, including the ever-changing landscape of business metrics, is vital for demonstrating the value of UX research. Furthermore, regularly reviewing the reliability and validity of psychometric properties ensures that these metrics maintain their scientific rigor. Lastly, addressing evolving cultural and contextual factors is essential to ensure the applicability of these tools in a global and diverse user base.